Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1124/jpet.115.225631
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineering Novel Chimeric microRNA-34a for Prodrug Cancer Therapy: High-Yield Expression and Purification, and Structural and Functional Characterization

Abstract: Development of anticancer treatments based on microRNA (miRNA/miR) such as miR-34a replacement therapy is limited to the use of synthetic RNAs with artificial modifications. Herein, we present a new approach to a high-yield and large-scale biosynthesis, in Escherichia coli using transfer RNA (tRNA) scaffold, of chimeric miR-34a agent, which may act as a prodrug for anticancer therapy. The recombinant tRNA fusion pre-miR34a (tRNA/mir-34a) was quickly purified to a high degree of homogeneity (.98%) using anion-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
140
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(156 citation statements)
references
References 43 publications
12
140
1
Order By: Relevance
“…However, research on miRNA pharmacoepigenetics and development of miRNA-based therapy may be limited by the utilization of synthetic miRNA agents consisting of excessive artificial modifications on the phosphate linkages and/or ribose rings and thus exhibit different physicochemical and biologic properties or toxicities. By contrast, recombinant RNA technology has been successfully employed to costeffectively produce large quantities of miRNA agents Chen et al, 2015;Li et al, 2015;Wang et al, 2015), which are comprised of no or posttranscriptional modifications on the nucleobases and may better capture the structures, functions, and safety properties of natural RNAs. These natural ncRNA agents are produced in cells and should represent a novel class of miRNA agents for research and development.…”
Section: Discussionmentioning
confidence: 99%
“…However, research on miRNA pharmacoepigenetics and development of miRNA-based therapy may be limited by the utilization of synthetic miRNA agents consisting of excessive artificial modifications on the phosphate linkages and/or ribose rings and thus exhibit different physicochemical and biologic properties or toxicities. By contrast, recombinant RNA technology has been successfully employed to costeffectively produce large quantities of miRNA agents Chen et al, 2015;Li et al, 2015;Wang et al, 2015), which are comprised of no or posttranscriptional modifications on the nucleobases and may better capture the structures, functions, and safety properties of natural RNAs. These natural ncRNA agents are produced in cells and should represent a novel class of miRNA agents for research and development.…”
Section: Discussionmentioning
confidence: 99%
“…Following the construction of target plasmid and transformation, target ncRNA is expressed in bacteria and purified to a high degree of homogeneity by anion exchange FPLC method. 40,43 We have further demonstrated that many chimeric ncRNAs (e.g., OnRS/miR-27b, OnRS/miR-124 and OnRS/GFP-siRNA, etc.) can be produced in E.coli on large scale, and be processed to target sRNA agents (e.g., miR-27b, miR-124 and GFP-siRNA, etc.)…”
Section: Bioengineering Of Rnai Agents In Vivomentioning
confidence: 90%
“…Bioengineered tRNA/mir-34a agent indeed acted as a prodrug in suppressing tumor growth in both subcutaneous A549 xenograft 43 and orthotopic 143B xenograft 45 mouse models, while BERAs were well tolerated in mice. Combined with DNA or protein targeting agents, RNA targeting BERAs could have synergistic effects to combat lethal cancer, especially those lacking effective target therapeutics.…”
Section: Bioengineering Of Rnai Agents In Vivomentioning
confidence: 99%
See 2 more Smart Citations